Integrated resource and environmental management: the human dimension - Ewert, A. W.; Baker, D. C.; Baker, D. C.; Bissix, G. C.; Bissix, G. C.; Ewert, A. W. (Wallingford :CABI Publishing, 2004)
This book consists of three sections (4 chapters each). Section 1 presents an overview and history of natural resource management, from both the North American and international perspectives. Section 2 discusses the challenges facing Integrated Resource and Environmental Management (IREM) by examining issues such as conflict, property rights, the role of social science in natural resource management, the influence and formation of power in a decision making context, and the theoretical foundations of IREM. Section 3 addresses the definition and application of IREM from several different contexts, including real-world applications and planning frameworks. Individual case studies are integrated into the end of each chapter, which serve to illustrate various models associated with IREM that demonstrate the advantages and challenges of using an IREM approach. In addition, discussion questions are included at the end of each chapter to stimulate dialogue underlying many of the issues presented in the text. This book has been written for students, primarily at the advanced undergraduate level, in the many academic areas pertaining to natural resource management. It provides a useful resource for practitioners, researchers and managers currently involved in the field of natural resource management, as well as providing a comprehensive aid for natural resource decision making within the context of the real world.
Keywords: EE115 - Natural Resource Economics, (New March 2000); PP000 - Natural Resources (General); UU485 - Social Psychology and Social Anthropology, (New March 2000); UU495 - Conflict, (New March 2000)